Experiential Learning Revisited: Lessons from a Student-Led Public Opinion Polling Class. Issue 3 (10th July 2020) - Rinfret, Sara R.; Angle, Justin; Scott, Samuel; Ward, Daisy; Yang, Kaixuan; Copeland, Emily; Power, Rebecca; Ray, Thomas; Hiett, Thomas
ABSTRACT: For decades, political and private polling operations have informed about the public's perceptions regarding a range of topics. In particular, universities (e.g., Marist and Quinnipiac) provide noteworthy research to inform and predict the outcomes of US elections. Yet, what role do our classrooms play in advancing the public opinion polling skills of our students? This article uses experiential learning as a descriptive framework to illustrate how a yearlong, immersive, and student-led public opinion polling experience, the Big Sky Poll, advances students' social-science and data-fluency skills. Our findings suggest important insights into the future of public opinion polling from the vantage point of a rural Western state, which can be replicated in other academic institutions.